ANALISIS SEMIOTIKA MAKNA LAGU "GALA BUNGA MATAHARI" KARYA SAL PRIADI - Husnusyifa, Annisa; Mujianto, Haryadi (TECHNO-SOCIO EKONOMIKA, 2024)
This study analyzes the lyrics of Sal Priadi's song "Gala Bunga Matahari" using Roland Barthes' semiotic approach. Music, as a universal language, allows for the conveyance of emotional messages and deep ideas through its lyrics. The study aims to identify signs within the song's lyrics and analyze the denotative, connotative, and mythological meanings of these signs. The method employed is a qualitative approach with descriptive interpretative analysis, involving documentation study techniques to gather data. Barthes' semiotic analysis is used to identify signs and explore their literal and symbolic meanings. The analysis reveals that sunflowers, plant language, and milk serve as symbols with rich meanings, conveying themes of longing, hope, and the desire to reunite. This symbolism enhances the understanding of the song's emotional narrative and resonates with listeners. The study provides deep insights into the meaning of "Gala Bunga Matahari" and its contribution to music and literary studies